PENDIDIKAN WAWASAN KEBANGSAAN DENGAN PENDEKATAN BAYANI DI PONDOK PESANTREN DARUL FALAH BANGSRI JEPARA - Rohman, Fathur (EDUKASIA, 2018)
The collision of the country versus the syari’at of Islam come back after the reform era. Pancasila is often accused as a kafir product because it is contradiction with syari’at of Islam. Responding to the phenomenon, Pondok Pesantren Darul Falah Bangsri Jepara provides the students with insight of nationality based on the point of view of Islamic teachings. This research tries to describe the education of nationality insight using bayani approach conducted by PP. Darul Falah. This research is a qualitative research with case study approach. The data were collected using participatory observation, in-depth interviews, and documentation. The data analysis techniques used are qualitative descriptive analysis with three steps. They are reduction, presentation, and ending with verification. The data analysis is conducted continuously from the beginning to the end of the research. The result of the research showed that the implementation of education of nationality insight using bayani approach is based on the emergence of propaganda that Pancasila is not in accordance with syari’at of Islam. Furthermore, there are three important elements of education of nationality insight using bayani approach. First, the teaching material is the text of the book Mitsaq al-Madinah or Pancasila book. Second, the method of learning uses bandongan, memorizing, and takraran. And third, the purpose of learning is understanding, memorizing, and attitude.